Does corruption starve Africa? The mitigating effect of political distribution of power - Henri Njangang Ndieupa; Simplice Asongu; Eric Mouchili (African Governance and Development Institute (AGDI), 2023)
Corruption remains a major challenge to sustainable economic growth, good governance, peace, and stability in both developed and developing countries. However, in developing countries, and particularly in Africa, hunger is another big challenge to inclusive economic development. To date, no empirical study has examined the effects of different types of corruption on hunger. Using three types of corruption (executive, legislative, and judicial corruption dynamics) and a panel of 45 African countries, this study contributes to the literature on the effects of corruption by examining, as a first attempt, the impact of types of corruption on hunger. We address the weak time-variance of our main regressors by using the most recent sequential linear panel dynamic estimator. The results show that countries with higher levels of executive, legislative, and judicial corruption are associated with a higher level of hunger. Moreover, the results show that executive corruption is the most disastrous for hunger in Africa, followed by legislative corruption. Our results remain valid even after using alternative measures of the key variables (hunger and corruption) and after controlling for the dynamic endogeneity using the generalized method of moments. Further analysis provides strong evidence that the political distribution of power across social groups mitigates the effect of corruption on hunger.
Keywords: P16; P35; O15; O55; 330; Corruption; Hunger; Power distribution among social groups; Africa